Insiders’ Voices: The Case of Informal Teacher Leaders in Lanao del Sur, Philippines - Madid, Minerva; Guimba, Wardah; Naga, Minerva-Saminah; Daguisonan, Lotis (Journal of Interdisciplinary Perspectives, 2024)
As part of the continuing efforts to contribute to the literature and studies on informal teacher leadership, this study aimed to explore and investigate the case of informal teacher leaders in Lanao del Sur and proposed an informal teacher leadership model generated from the findings. This study utilized a qualitative approach and employed a case study design. To holistically understand the case, twenty-four informal teacher leaders from different secondary schools were purposively identified and recommended to participate in the study. The data were gathered through focused-group interviews, personal narratives, and observations and were analyzed through Thematic Analysis. The findings unveiled that leadership and informal teacher leadership are defined as a skill or a process of mobilizing people toward attaining goals. The findings also discovered developed leadership attitudes and skills essential for effective and successful leadership. Besides, these informal teacher leaders encountered conditions that encouraged or discouraged them from taking leadership roles and accepting additional duties and responsibilities. From these findings, an informal teacher leadership model was generated. This model could be adopted and properly implemented to formally recognize and increase informal teacher leaders, nurture and harness their potential, and motivate them to take leadership roles because they foster a culture of collaboration, innovation, and continuous teaching and learning improvement in schools.